Coastal latrine sites as social information hubs and drivers of river otter fission–fusion dynamics. (October 2016) - Barocas, Adi; Golden, Howard N.; Harrington, Michael W.; McDonald, David B.; Ben-David, Merav
Abstract : Fission–fusion dynamics, consisting of regular shifts in the size and composition of social groups, are prevalent in animal societies and have implications for foraging success, disease and information transfer, and the fitness of individuals. Thus, the individual and environmental factors that drive social dynamics have become a focus of recent investigations. River otters, Lontra canadensis, in coastal Alaska have a plastic social system, influenced by forage fish availability. These carnivores also regularly frequent terrestrial latrine sites, where they associate and communicate through deposition of odorous substances. To investigate fission–fusion dynamics in this system we (1) deployed camera traps to record social behaviours at latrine sites and (2) attached proximity tags to quantify encounter rates among individuals. Camera detections demonstrated that most latrine visits were of single otters and small groups (2–8 individuals). Fusion events into large groups (up to 18 individuals) were infrequent. Larger groups were recorded at crossover latrines, where trails connected bodies of water, whereas social behaviour was more frequent at spatially central latrines. Visiting otters performed signalling behaviours more frequently than social behaviours, especially at crossover sites. Proximity tag data revealed that the timing of fission and fusion events coincided with latrine visits and that spatial overlap was a good predictor of social interaction. Thus, the structural and spatial features of latrines influence their function as centres of information exchange, social activity hubs and meeting places among small social units, with implications for river otter group dynamics. We conclude that shifting social and environmental conditions may lead to high communication complexity. This unique social system provides novel evidence of the role of olfactory communication in mediating social decisions. Highlights: We studied how scent marking affects the social system of coastal river otters. Larger groups were found at trail-dominated crossover latrines. Social behaviour was more frequent at latrines with high spatial centrality. Latrine visits were temporally associated with fission–fusion events. Sensory communication may affect grouping decisions in fission–fusion societies.